Imogolite: A Nanotubular Aluminosilicate: Synthesis, Derivatives, Analogues, and General and Biological Applications - Escudey-Castro, A; Escudey-Castro, A; Arancibia-Miranda, N; Arancibia-Miranda, N; Tasca-Gottardo, F; Tasca-Gottardo, F (Royal Society of Chemistry, 2021)
Imogolite is an aluminosilicate mineral originally found in volcanic ash derived soils. Through the use of chemical synthesis methods this mineral has been successfully synthesized and a number of modified similar nanomaterials have also been produced. Due to its nanotubular arrangement this mineral shows a similar structure to carbon nanotubes and as such has been investigated for possible applications in a range of fields like polymer composites, gas storage, adsorption and catalysis. This review will start with an introduction to the basic characteristics of imogolite, followed by the synthetic methods of production, techniques for the production of composite and hybrid materials, characterization, potential applications, and, finally, biological applications, focusing particularly on composites with biological molecules and interactions with living cells as well as toxicological activity. This journal is © the Partner Organisations.